Konsep Mahabbah Rabi'ah Al-Adawiyah - Kamaruddin Mustamin (LPPM IAIN Sultan Amai Gorontalo, 2020)
In sufistic discourse, the real journey of life can be said to be a journey to seek God and at the same time a journey to God or at least to God. When the endeavor in that direction is taken seriously, then there are three potential choices that can be made by someone who believes in the existence of God based on the three basic potentials that humans have. If someone is trying to use her services with the potential of using her services, she will strive (mujahid) and try to become a martyr in the way of Allah. If he maximizes the potential of his mind, then he will emigrate with his reasoning power to get closer to the divine truth. If he tries to use his Ruhiyah potential, he will worship to upgrade his piety to the Creator. Rabi'ah al-Adawiyah seems to have sought his sincerity to approach and approach God in a third way. Through the concept of mahabbah that he coined, Rabi'ah al-Adawiyah consistently upgraded his love from ordinary love to extreme love. This effort has tremendous implications for the presence of expressions of love for Allah without any conditions or tendencies. With this extreme expression of love, Rabi'ah believes that she can meet and unite with the Creator. This concept might be judged to leapfrog the epistemology of the Shari'a, but it is personally worthy of being valued as an endeavor that utilizes the spiritual power that potentially belongs to Allah swt., entrust every human being.